The Diversity of Macroscopic Fungi in The Education Forest of University of Sumatera Utara, Tongkoh Village, Karo District, North Sumatra Province - Santa Dewi Bornok Mariana Tampubolon; Budi Utomo; Yunasfi Yunasfi (Peronema Forestry Science Journal, 2013)
The research of the diversity of macroscopic fungi in Education Forest of University of North Sumatra has never been reported. The research has been conducted at altitude: < 1000 m above sea level; 1000 – 1500 m above sea level; and ≥ 1500 m above sea level, on five different trail on each altitude category. The length of observation trail is 100 m. The first trail on each altitude category is determined with purpossive sampling method, then the next trail was determined with systematic sampling method. The observation and the collection of species has done exploratively in the plot sampling, size 20 m x 20 m. The results showed that was found 45 species of macroscopic fungi which consist of 2 divisions, 4 classes, 10 orders, and 19 families, where numbers of species of macroscopic fungi was found on each of altitude category consecutively 30 species; 42 species; and 32 species. The macroscopic fungi was found commonly living on the decayed wood and litter, and then a part of living on the living wood. Keywords : Macroscopic fungi, diversity of macrofungi, Basidiomycota, Education Forest of University of North Sumatra.